2015
DOI: 10.1002/mc.22446
|View full text |Cite
|
Sign up to set email alerts
|

A Zbtb7a proto‐oncogene as a novel target for miR‐125a

Abstract: In our previous study, we showed that miR-125a directly targeted a WT1 oncogene, which was overexpressed in leukemia and various kinds of solid tumors including lung, breast, gastric, and colon cancers, and brain tumors and was deeply involved in leukemogenesis and tumorigenesis and that miR-125a knockout mice overexpressed WT1 and developed myeloproliferative disease. It had been also reported that miR-125a is downregulated in leukemia and various types of solid tumors such as lung cancers, suggesting its tum… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
23
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(23 citation statements)
references
References 52 publications
0
23
0
Order By: Relevance
“…The presence of an association between ZBTB7A downregulation and poor patient survival further support for the importance of ZBTB7A alterations in HNSCC. In previous studies, miR-20a, miR-100 and miR-125a have been shown to be suppressor miRNAs that are able to reduce expression of the ZBTB7A proto-oncogene in tumors (26)(27)(28). However, it has been found that miR-106b targeting of ZBTB7A increases the survival of hepatocellular carcinoma cells (25).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The presence of an association between ZBTB7A downregulation and poor patient survival further support for the importance of ZBTB7A alterations in HNSCC. In previous studies, miR-20a, miR-100 and miR-125a have been shown to be suppressor miRNAs that are able to reduce expression of the ZBTB7A proto-oncogene in tumors (26)(27)(28). However, it has been found that miR-106b targeting of ZBTB7A increases the survival of hepatocellular carcinoma cells (25).…”
Section: Discussionmentioning
confidence: 99%
“…Although the roles of ZBTB7A in carcinogenesis are controversial and the mechanisms by which it acts remain largely obscure, frequent deletion and downregulation of ZBTB7A has been shown to occur in a range of malignancies including OSCC (20,(23)(24)(25). In addition, miR-106b and other miRNAs have been shown to target ZBTB7A in such malignancies (25)(26)(27)(28).…”
Section: Introductionmentioning
confidence: 99%
“…In mammalians, miR-125a appears to be expressed in most tissues, mainly targeting membrane receptors or intracellular signal transductors of mitogenic signals, thus limiting cell proliferation. Expression of this miRNA generally increases with cell differentiation whereas it is downregulated in several types of tumors, such as breast [2527], lung [32, 33], ovarian [40], gastric [41], colon [42], and cervical [43] cancers, neuroblastoma [29], medulloblastoma [30], glioblastoma [31], and retinoblastoma [44]. Limited studies on the expression of miR-125a in HCC have also been performed.…”
Section: Discussionmentioning
confidence: 99%
“…In particular, 200 ng of RNA were retrotranscribed by Transcriptor High Fidelity cDNASynthesis Sample kit (Roche) using random examer primers; 1 μl of cDNA product was then used to amplify the target sequences along with GAPDH as reference. Primers were: GAPDH, 5′-GAAGGTGAAGGTCGGAGTC-3′ and 5′-GAAGATGGTGATGGGATTT-3′; SIRT7, 5′-GTCTG CATGAGCAGAAGCTG-3′ and 5′-GGAACGCAGGA GGTACAGAC-3′; c-Raf, 5′-GCAATGAAGAGGCTGGT AGC-3′ and 5′- GGAGCAGCTCAATGGAAGAC-3′; Zbtb7a, 5′-ACGAGTGCAACATCTGCAAG-3′ and 5′-GG TCGTAGTTGTGGGCAAAG-3′ [33]; MMP11, 5′-TCC TGACTTCTTTGGCTGTG-3′ and 5′-CCATGGGTCT CTAGCCTGAT-3′ [35]. The expression levels of miR-125a and its targeted transcripts were normalized to their respective reference genes by using the 2 −ΔCt method.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation